Assessment of IL-31 levels and disease severity in children with atopic dermatitis - Ozceker, D.; Bulut, M.; Ozbay, A. Celik; Dilek, F.; Koser, M.; Tamay, Z.; Guler, N. (My University, 2018)
Introduction and objectives: Atopic dermatitis is a chronic, relapsing, highly pruritic, inflam- matory skin disease characterized by typical localization with increasing prevalence of 10-20% in children. Pruritus is one of the major diagnostic criteria of atopic dermatitis and also the main complaint altering quality-of-life of affected patients, inducing and aggravating inflammation. Although pruritus is the absolute symptom of AD, the etiology has not been fully explained yet and current antihistamine therapies are ineffective.